Perilaku Manajemen Agribisnis Peternak Kombinasi Sapi Potong Dan Kambing Di Kecamatan Sendang - Ningsih, Dwi Aminawati; Sumarji, Sumarji; Daroini, Ahsin (Universitas Islam Kadiri, 2025)
The research aim is to describe of the agribusiness management behavior of combination beef cattle and goat breeders in Sendang District, Tulungagung Regency. Research was carried out in Sendang District. Data collection by observation, interview and documentation. The method used qualitative and descriptive analysis. Agribusiness management by breeders is in accordance with the experience they have. Agribusiness management includes housing, selection (Grading), feeding and drinking, mating systems, sanitation and disease control, waste treatment and marketing. Farmers in agribusiness management are lacking in providing food and drink as well as waste treatment.